INFORMED CONSENT AS A LEGAL PROTECTION FOR PATIENTS: PERLINDUNGAN HUKUM TERHADAP PASIEN MELALUI PERSETUJUAN TINDAKAN MEDIK - Eutheriana, Raden Roro Anja (Dentika: Dental Journal, 2016)
Informed consent is a communication process between doctors and patients pertaining an agreement about medical treatments performed by doctors to their patients then continued by signing informed consent form. It originates from the legal and ethical right the patient has to direct what happens to her body and from the ethical duty of the physician to involve the patient in her health care. The most important goal of informed consent is that the patient has an opportunity to be an informed participant in his health care decisions. Informed consent usually also protects doctor from liability (with exceptions) provided that the procedure is properly execute according to the prevailing standard of care without negligence. Approval for informed consent must be based on medical information regarding the disease from the relevant medical doctors. This matter is regulated in Article 45 of Law 29 of 2004 about medical practices. It can be concluded that an informed consent is one of legal efforts in protecting patients from medical neglect that medical doctors commited.